Family Education in Working Mothers Families: Case Study of Mothers Who Work as Civil Servant - Ade Yusuf Ferudyn; Kusnida Indrajaya; Endah Yusma Pratiwi; Hendrowanto Nibel; Susan Daniel (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: The role of women in the family has evolved, with more women working outside the home in response to economic and social demands. Consequently, women face dual roles, balancing domestic responsibilities with work demands. This double burden affects their informal educational responsibilities towards their children. As a result, both fathers and mothers spend more time at work and return home tired, reducing time available for educating their children. Aim: This study aims to explore the family education process in families with mothers who work as Civil Servants and to identify challenges in children's education. Method: This research uses a qualitative approach with a case study design. The findings indicate that working mothers strive to be involved in their children's education despite time constraints, consistency in emotional interactions, and teaching moral values. Result and Disscusions: Informants attempt to maximize quality time on weekends and interact before bedtime, though emotional involvement is often hindered by work demands. Care from third parties, such as grandparents or professional caregivers, provides emotional stability but may create inconsistencies in the values desired by parents. Conclusion: In conclusion, despite the challenges in family education for working mothers, effective time management strategies, open communication with caregivers, and being a good role model are essential for optimal child education.